Knockdown of Angiopoietin-like protein 4 suppresses the development of colorectal cancer - Wen, Liqiang; Zhang, Yuchao; Yang, Bin; Han, Fanghai; Ebadi, Abdol Ghaffar; Toughani, Mohsen (Cellular and Molecular Biology, 2020)
Colorectal cancer, is the growth of cancer cells in the part of the colon. Angiopeptin is one of the growth factors in the human body that is particularly effective in the regulatory process. In this research, the regulatory role and its mechanism of Angiopoietin-like protein 4 (ANGPTL4) in colorectal cancer (CRC) metastasis, has been studied. Protein expression of ANGPLT4 was analyzed by immunohistochemistry in tumor samples and adjacent normal specimens of 40 patients with CRC cancer of various phases. A gene knockout test was conducted, two effective siRNA of ANGPTL4, named siRNA1 and siRNA2, were constructed and transfected into two CRC cell lines SW480 and HT-29 to block the expression of ANGPTL4. QRT-PCR and western blotting were used to validate the knockdown efficiency of the mRNA and proteins. Based on the results, the protein expression of ANGPTL4 was increased in human CRC tissues with the development of CRC. Knockdown of ANGPTL4 by siRNA in SW480 and HT-29 cells in vitro inhibited cell proliferation, promoted cell apoptosis, and suppressed the ability of cell migration and invasion. Besides, the sensitivity of CRC cells to Cisplatin was increased in the low ANGPTL4 expression group. ANGPTL4 might be a new potential therapeutic target for patients with CRC.